Pengaruh Kecerdasan Emosional, Komunikasi Interpersonal, dan Lingkungan Kerja terhadap Kinerja Pegawai PT. PLN (Persero) Up3 Surakarta: Studi Kasus PT PLN (Persero) Up3 Surakarta - Awang Adi Saputro; Sudarwati, Sudarwati; Maryam, Siti (MES Bogor, 2024)
To_analyze_the influence of emotional intelligence, interpersonal communication and work_environment_on_employee_performance at PT PLN (Persero) UP3 Surakarta, this research is a qualitative descriptive study with primary data type. The population is 120 people, therefore the_sample_taken from this population must be truly representative, namely 53 people. Data_collection methods use questionnaires, interviews, and documentation of questionnaire data. The sampling technique is probability sampling, strengthened by simultaneous tests, partial tests, multiple linear regression tests, and coefficient of determination tests. The research results show that emotional intelligence has a significant positive_effect, _interpersonal_communication_has a significant positive effect, the work environment does not have a significant effect on the performance of PT PLN (Persero) UP3 Surakarta employees. The research tool uses SPSS Statistics 26